2019
DOI: 10.1242/dev.181644
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of LST-1 self-renewal activity and its control of stem cell pool size

Abstract: PUF RNA-binding proteins have diverse roles in animal development, with a broadly conserved role in stem cells. Two paradigmatic PUF proteins, FBF-1 and FBF-2, promote both self-renewal and differentiation in the C. elegans germline. The LST-1 protein is a pivotal regulator of self-renewal and is oncogenic when misexpressed. Here, we demonstrate that LST-1 self-renewal activity resides within a predicted disordered region that harbors two KXXL motifs. We find that the KXXL motifs mediate the binding of LST-1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(117 citation statements)
references
References 64 publications
5
112
0
Order By: Relevance
“…Fourth, LAG-1 binding sites in a sygl-1 promoter reporter are required for distal germline specific expression [20] and similarly, the LAG-1 binding sites in a lst-1 reporter are required for LIN-12 Notch dependent expression in a somatic cell context [23]. LST-1 and SYGL-1 act, at least in part, through binding to Pumilio family RNA binding proteins FBF-1 and FBF-2 that function in mRNA degradation and translational repression of the gld-1 meiotic entry pathway genes [22,[24][25][26][27].…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, LAG-1 binding sites in a sygl-1 promoter reporter are required for distal germline specific expression [20] and similarly, the LAG-1 binding sites in a lst-1 reporter are required for LIN-12 Notch dependent expression in a somatic cell context [23]. LST-1 and SYGL-1 act, at least in part, through binding to Pumilio family RNA binding proteins FBF-1 and FBF-2 that function in mRNA degradation and translational repression of the gld-1 meiotic entry pathway genes [22,[24][25][26][27].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…LST-1 and SYGL-1 have been reported to function in conjunction with FBF-1 and FBF-2 in direct translational repression/mRNA destabilization in the posttranscriptional inhibition of GLD-1 accumulation [22,27]. FBF-1 has also been shown to function in translational repression/mRNA destabilization in the posttranscriptional inhibition of FBF-2 accumulation [30].…”
Section: Glp-1 Signaling Indirectly Mediates Control Of Rna and Protementioning
confidence: 99%
“…The assay investigating binding of FBF-2 PUF domain to target mRNA in the presence of a 40-amino-acid fragment of CPB-1 outside of the RNA-binding domain demonstrated that association with CPB-1 fragment alters FBF's preference for specific RNA sequences (Campbell et al, 2012;Menichelli et al, 2013). Additional FBF interaction partners include novel proteins SYGL-1 and LST-1 that are required for FBF-dependent target mRNA repression in germline SPCs (Kershner and Kimble, 2010;Brenner and Schedl, 2016;Shin et al, 2017;Haupt et al, 2019a). Using SEQRS (in vitro selection, high-throughput sequencing of RNA, and sequence specificity landscapes), analysis of RNA-binding preference of FBF-2 PUF domain bound to a 150-amino-acid LST-1 fragment FIGURE 3 | Modification of FBF biological activity though interactions with protein partners.…”
Section: Protein Cofactors That Change Rna Target Preferencementioning
confidence: 99%
“…Fluorescence intensity was measured in FIJI using previously described methods 25,72 . OLLAS and V5 intensities were normalized to the N2 background.…”
Section: Mpk-1 Protein Quantificationmentioning
confidence: 99%
“…1A, right). A pool of proliferative GSCs is maintained at the distal end within a somatic niche; as GSC daughters leave the niche, likely displaced by proliferation, they begin differentiation and progressively mature into gametes at the proximal end 20,[23][24][25][26] . GSCs, together with their proliferating progeny, span a region in the distal gonad termed the progenitor zone (PZ) ( Figure 1A, right).…”
Section: Introductionmentioning
confidence: 99%